A Analisis Kandungan Logam Berat Pada Krim Pemutih di Kota Banjarmasin - I Ketut Gunawan Kusuma; Nur Hidayah; Tuti Alawiyah (Jurnal Pelayanan Kefarmasian dan Sains, 2021)
Background Whitening cream is a mixture of chemicals or other material which is able to whiten the skin. The presence of heavy metals such as Hg and Cd in the whitening cream products are very dangerous, because if the heavy metal ions adsorbed into tissue and organs, it will cause health problems. Objective This study aims was to find out the properties and levels of heavy metals mercuri and cadmium in the sample of the bleach cream in Banjarmasin. And to find out whether heavy metals in mercury and cadmium exceed the statute limit by the National Agency of Drug and Food Control of the Republic of Indonesia BPOM RI No. 12 tahun 2019. Method The study USES a method of analytic observation with a cross sectional design. The sample of the bleach cream used was a cream-bleach product with no license of The food and drug administration. As many as five samples of bleach cream were purchased at random in three markets that were on Banjarmasin analyzed using atomic absorption spectrophotometer. Results Research shows the highest hg concentration of metal showing on a sample of bleaching cream with a code E 0.675 Âµ /kg, the highest cd-metal content showing on the sample of the bleach code C 0.994 mg/kg. Conclusion: The result is under the limit set by the terms by the National Agency of Drug and Food Control of the Republic of Indonesia BPOM RI No. 12 tahun 2019. Keyword: Atomic Absorption Spectrophotometer, Heavy Metal, Whitening Cream